Formation of a viscoelastic dough from isolated total zein (α-, β- and γ-zein) using a glacial acetic acid treatment. (September 2016) - King, Bianca L.; Taylor, Janet; Taylor, John R.N.
Abstract: Only predominantly α-type zein (commercial zein) has been shown to form a viscoelastic dough. In maize zein comprises α-, β-, γ- and δ-zein (total zein). Because glacial acetic acid can fully solubilise zein, its effect was investigated. Dissolving total zein (comprising α-, β-, γ- and δ-zein) in glacial acetic acid and casting a film, enabled a viscoelastic dough to be formed with water above zein's Tg . The dough was stronger and less extensible than commercial zein dough made without film formation. When residual acetic acid was removed from the total zein film, a dough still formed. CLSM showed that the total zein dough fibrils were shorter and less well-aligned than those of commercial zein dough and appeared as particles. Disulphide bond cross-linking was probably responsible, for total zein dough stiffness. FTIR showed that total zein wet doughs and total zein slurry with water were predominantly β-sheet, indicating that β-sheet conformation was not directly responsible for dough formation. It is suggested that acetic acid brings about chemical changes in zein, enabling it to better interact with water molecules, counteracting disulphide bonding effects, allowing total zein to form a dough. This is the first report of viscoelastic dough formation from total zein. Highlights: First report of viscoelastic dough formation from total zein, α, β, δ and γ zein. Dough was formed by dissolving total zein in glacial acetic acid and casting a film. On stretching, total zein dough comprises short fibrils made up of particles. Wet total zein dough is predominantly in β-sheet conformation. Total zein dough is less extensible than α-zein dough, probably due to S-S crosslinks.